A follow up study on the efficacy of metadoxine in the treatment of alcohol dependence - Gentili Claudio; Guerrini Irene; Nelli Gloria; Guazzelli Mario (BMC, 2006)
Abstract Background We carried out a three months follow-up study on the efficacy of metadoxine in a cohort of alcoholics admitted to the Alcohol misuse Long-term Treatment (ALT) Unit - University of Pisa (Italy). We analyzed the clinical data, psychometric tests and blood tests of 160 alcoholics on admission and after 3 months of treatment. We compared 58 pts treated with metadoxine (MET) with 102 pts who did not receive (NULL) any drug as an adjunct to the psycho-educational interventions provided by the ALT Unit. Results At follow-up, the patients in treatment with metadoxine showed a significant improvement in the rate of complete abstinence (44.8% vs. 21.6%; chi square: 8.45, df = 1, p < 0.0037). Furthermore, the number of drop-outs at three months of treatment was also significantly lower in the MET than in the NULL group (17% vs. 57%; chi square of 23.22, df = 1, p < 0.001). Conclusion Our findings support the use of metadoxine in the management of alcohol dependence. However, randomized clinical trials are necessary to confirm and replicate them. This study raises the importance of identifying new pharmacological compounds effective on the outcome of alcoholism in order to help patients to best adhere to treatment programs and to prevent the development of mental and physical complications due to chronic and heavy use of alcohol.